KOMPETENSI PROFESIONAL GURU DAN ETOS KERJA PENGARUHNYA TERHADAP KINERJA GURU - Tatang (MADINASIKA, 2020)
This research is motivated by the phenomenon of low teacher performance, marked by the unfulfilled all the elements forming professional teacher standards. This is thought to be the result of low levels of teacher professionalism and work ethic. The research aims to find out; a) teacher professional competence, work ethic, and teacher performance; b) the magnitude of the professional influence of teachers on teacher performance; c) the magnitude of the influence of work ethic on teacher performance; and d) the magnitude of the influence of teacher professional competence and work ethic on teacher performance. This research uses a quantitative approach with a survey method. The data collection tool used a questionnaire distributed to 80 respondents consisting of vocational school teachers. The data obtained were analyzed using a parametric statistical approach. Descriptively, the results showed that the professional competence of teachers, work ethic, and teacher performance were in good condition, but there were still weaknesses in certain aspects. From the results of the verification analysis: a) teacher professional competence partially affects teacher performance; b) work ethic partially affects teacher performance; c) teacher professional competence and work ethic simultaneously influence teacher performance with a magnitude of influence of 75,50%, the remaining 29,50% is influenced by other factors. In conclusion, teacher professional competence and work ethic both partially and simultaneously affect teacher performance.